2011
DOI: 10.1590/s0004-282x2011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Odors as triggering and worsening factors for migraine in men

Abstract: Objective: To assess the role of odors in triggering or worsening migraine in men. Method: Ninety-eight male migraineurs from the general population were assessed individually through questionnaires. Environmental factors relating to their migraine were reported, with special focus on the role of odors. Results: Odors were the second most frequent triggering factor for migraine attacks (48%), behind stressful situations (59%). Likewise, odors were the second most frequent worsening factor (73%), just behind ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 18 publications
4
34
0
2
Order By: Relevance
“…Several components of cigarette smoke, such as acrolein, crotonaldehyde [78], acetaldehyde [37] and nicotine [101], are TRPA1 agonists. Recently, acrolein application to the rat nasal mucosa has been shown to produce ipsilateral meningeal vasodilatation by a TRPA1- and CGRP-dependent mechanism [102], thus offering a mechanistic explanation for the association between the exposure to cigarette smoke and migraine attack appearance or worsening [103,104]. …”
Section: Reviewmentioning
confidence: 99%
“…Several components of cigarette smoke, such as acrolein, crotonaldehyde [78], acetaldehyde [37] and nicotine [101], are TRPA1 agonists. Recently, acrolein application to the rat nasal mucosa has been shown to produce ipsilateral meningeal vasodilatation by a TRPA1- and CGRP-dependent mechanism [102], thus offering a mechanistic explanation for the association between the exposure to cigarette smoke and migraine attack appearance or worsening [103,104]. …”
Section: Reviewmentioning
confidence: 99%
“…Clinical reports have indicated that inhalation of TRPA1 irritants can trigger migraine headache with a high frequency in susceptible individuals [15,19,28,45,60]. Exposure to the scent of Umbellularia californica (aka “the headache tree”) can produce cluster-like headache attacks in humans [8] and the principal volatile component of the plant, umbellulone, was recently identified as a TRPA1 agonist [42,59].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, distinguishing between enhanced sensitivity to smells in the early phase of the attack, before pain has started, and olfactory stimulation as a trigger is challenging [63]. In a study including 96 male migraineurs, Marmore de Lima et al found that odors, especially perfume, cigarette smoke and cleaning products, were the second most frequently reported trigger (48%) following stress (59%) [64]. Silva-Neto et al interviewed 400 headache patients, 200 with migraine and 200 with tension-type headache, regarding odorant substances as headache precipitant [65].…”
Section: Odorsmentioning
confidence: 99%